Espacialização dos processos minerários na Região Metropolitana de Belém - Pará - MAIA, Raquel da Silva Vieira (2022)
Mining is an activity that has intensified over the years. Thus, to measure the exploratory activities arising in the Metropolitan Region of Belém - Pa, the research proposed through geoprocessing the spatialization of mining processes. In this one, research was carried out in the database provided by the Geographic Information System for Mining (SIGMINE) of the National Mining Agency (ANM), to produce a space-time survey, aiming to characterize the municipalities that have the highest concentrations of areas required to the agency competent. For data diagnosis, maps were made to represent the required polygons, in addition to the use of the Kernel density method, operating the QGIS software with data from the period from 2001 to February 2022, to determine the behavior in the advances of mining interests, in addition to of the production of graphic representations. As a result, 157 polygonal mining processes were spatialized for different mineral substances, predominantly found in licensing phases, applied in civil construction, expressing greater concentrations of areas for mineral water extraction and with a greater number of processes in the municipalities of Santa Izabel, Benevides and Castanhal, regarding the quantity of areas in hectares, the municipality of Santa Izabel surpasses the others, as some areas were required through cooperatives, through the requirement of mining for areas with almost 10,000 hectares. Therefore, it was identified that the study area has undergone significant advances over the years for such activities, comprising in all almost eighty-two thousand hectares in required areas, thus making it an object of mineral exploitation.